Evolução estrutural do depósito aurífero Cuiabá e perspectivas exploratórias circunjacentes, Quadrilátero Ferrífero, Brasil - Raphael do Carmo Fernandes (2022)
The structural architecture of an orogenic deposit is essential for its metallogenetic understanding, as both subjects are interconnected in this type of environment. Cuiabá gold deposit, located in Archean rocks from Rio das Velhas Greenstone belt, is the subject of numerous studies focused mainly on metallogenetic issues. These mineralizations are hosted essentially at sulfides inside banded iron formations and surrounded in schists of mafic composition. From the point of view of structural characterization, two divergent models have been studied: the sheath-fold model and the refolding model, bringing different exploratory perspectives to the region. As a way of filling this gap, the main objective of this work is to characterize the geology and define a new deposit model so that there is a better understanding of its framework. For this, the methodologies applied for this work were: underground geological mapping in accessible ore galleries and definition of geological-structural domains whose main criteria are related to down-plunge view of fold asymmetry and stratigraphic indicators in the fold symmetry plane. Structural geology is characterized by 3 deformation phases related to 2 tectonic events. The first event has two ductile-progressive deformation phases (D1 and D2), with NE-SW strike-slip direction of transport associated coaxial fold interference patterns with cylindrical geometry plunging to ESE, which represents the main structure and gold mineralization at the mine. The second event is a brittle-ductile deformational phase (D3) with W-verging reverse fault systems, probably associated to Brasiliano Pan-African Orogeny. Gold mineralization is associated with silica and sulfide-rich hydrothermal fluid introduction through D1 and D2 axial-plane foliation. Phase D1 is pyrrhotite-associated mineralization, with coarse gold presence (from 50 to 500 μm). D2 phase has pyrite-associated mineralization with fine gold (from 10 to 100 μm). There is no gold in phase D3, although it has late tectonic sulfide formation. Field observations demonstrate the existence of coaxial refolding patterns associated with mineralization, constant fold axes plunging to ESE, absence of sheath folds and preserved sedimentary structures. Therefore, there is no field evidence that corroborate the existence of sheath folds for the deposit. Fold interference patterns associated to deposit morphology suggests SW and N prospective targets, with strong possibility of structural connection between other gold deposits, such as Lamego and Descoberto targets.